Industry- and liquidity-based momentum in Australian equities - Yeng-May Tan; Fan Fah Cheng (Financial Innovation, 2019)
This study examined momentum profitability in Australia, providing further evidence for intermediate-term momentum profitability. Using data spanning different market states, we found that momentum was stronger after the global financial crisis. We also examined industry-level momentum strategies and found strong evidence for industry momentum. Specifically, industries that perform well relative to other industries continue to outperform others while those that underperform continue to perform poorly. This finding suggests the exploitability of return continuation and profit-making opportunities for traders at the industry level. Regarding liquidity, we found that it has no clear predictive power for momentum returns. Hence, our results do not appear to support the conjecture that liquidity can be a determining factor for momentum profitability in Australia.
Keywords: 650; Momentum strategy; Stock momentum; Industry momentum; Liquidity; Market states; Australia